Report on Evaluation Study of Centrally Sponsored Package Programme for Jute - Planning Commission (Planning Commission, 1978)
Although, the jute development programme was initiated as early as the beginning of the Second Five Year Plan, the yield has remained subject to wide fluctuation. The Government of India launched Special Package Programme for Jute as a pilot project in 1968-69 with a view to increase the unit yield, especially of superior quality fibre. The scheme envisaged to saturate the selected areas with all the development inputs, such as improved seeds, foliar spraying, adoption of correct retting practices and extraction of fibre, to motivate the growers to adopt scientific techniques of farming and grading of fibre.
Programme Evaluation Organisation Planning Commission Government of India